Haryana State Draft Annual Plan 1978-79 (In 4 Volumes) Vol. IV - Planning Commission (Planning Commission, 1977)
The Planning Commission, Government of Indic originally approved a total provision of Rs. 1440.00 lacs for the Fifth Five Year Plan of the Industries Department which s subsequently reduced to Rs. 1271 46 lacs by the State Planning Department. Out of this an outlay of Rs. 188.80 lacs, Rs. 154.80 lacs and Rs. 224.00 lacs Was for the years 1974-75, 1975-76 and 1976-77 respectively. Against these provisions the expenditure incurred amounted to Rs. 191.66 lacs, has. 157.23 lacs and Rs. 195.14 lacs respectively during the first three years of the Fifth Plan. It is anticipated that the provision of its. 247.89 lacs for the current financial year will also be fully utilized.
Government of Haryana
Planning Department Government of Haryana
Keywords: Road Transport; Department of Tourism Haryana; Department of Industrial Training Haryana; Health Department Haryana; Medical Education; Housing; Public Relations Department; Department of Employment Haryana; Welfare of Scheduled Castes Backward Classes Department Haryana; Other General Economic Services; Economic Advice and Statistics